Dynamic distributed flexible job-shop scheduling problem considering operation inspection - Zhu, Kaikai; Gong, Guiliang; Peng, Ningtao; Zhang, Liqiang; Huang, Dan; Luo, Qiang; Li, Xiaoqiang (Expert systems with applications, 2023)
The classical distributed flexible job-shop scheduling problem (DFJSP) only considers static manufacturing environment and ignores operation inspection. However, in the real production, the manufacturing environment is normally dynamic and the operation inspection is very important to prevent unqualified products from being transported to the next manufacturing stage. In this paper, we first propose a dynamic distributed flexible job-shop scheduling problem considering operation inspection (DFJSPI). A modified memetic algorithm (MMA) is then designed to solve the DFJSPI aiming at to minimize the makespan and total energy consumption. In the MMA, a novel five-layer encoding method and an initialization method are developed to generate a high-quality initial population. A hybrid rescheduling method including three rescheduling strategies is developed to handle different inspection results. Some effective crossover operators, mutation operators and a local search operator are designed to expand the solution space of MMA and to accelerate its convergence speed. A total of 100 DFJSPI benchmark instances are constructed to test the performance of the MMA. Extensive experiments carried out to compare the proposed MMA with other three well-known algorithms demonstrate that the MMA has obvious superiority in almost all tested instances. This study will be beneficial for the production managers to deal with dynamical distributed manufacturing with operation inspection, especially providing reference for the manufacturing systems with operation reworking and scrapping.